Preparation and application of block cationic copolymer quaternary ammonium salt chitosan-based composite hydrogel

Through the preparation of block cationic copolymer/quaternary ammonium salt chitosan-based composite hydrogel, combined with electrostatic and photothermal synergistic sterilization technology, the instability and limitation of antibacterial activity of hydrogel dressings in extreme environments is solved. , achieving efficient bacterial killing and wound healing effects.

CN119192612APending Publication Date: 2024-12-27GUIZHOU MEDICAL UNIV
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411327526.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing hydrogel dressings are unstable in extreme environments, prone to water loss or hardening, and their antibacterial activity is limited by contact area and time, resulting in drug resistance problems and affecting the wound healing effect.

Method used

Using block cationic copolymer/quaternary ammonium chitosan-based composite hydrogel, by introducing oxidized sodium alginate, acrylamide, 1-butyl-3-vinyl imidazole ammonium bromide and 3-acrylamide phenylboric acid The photothermal agent MXene-Ag-PDA is added to improve antibacterial activity and anti-freeze-and-drying properties through electrostatic action and photothermal synergistic sterilization.

Benefits of technology

It achieves efficient bacterial killing, avoids bacterial resistance, enhances the stability and healing ability of hydrogels in extreme environments, and significantly improves the application effect of wound dressings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192612A_ABST
    Figure CN119192612A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel. The preparation method comprises the following steps: reacting a sodium alginate solution with a NaIO4 solution at room temperature in a dark place to obtain an oxidized sodium alginate solution; adding ethylene glycol into the oxidized sodium alginate solution, reacting, concentrating, dialyzing and drying to obtain oxidized sodium alginate; the preparation method comprises the following steps: mixing acrylamide, 1-butyl-3-vinyl imidazole ammonium bromide, 3-acrylamide phenylboronic acid and quaternary ammonium salt chitosan, dissolving in water, adding ammonium persulfate and N, N-methylene bisacrylamide, heating for reaction, and cooling to obtain a cooling liquid; adding the oxidized sodium alginate solution into the cooling liquid, continuously adding polymerized N, N, N ', N'-tetramethylethylenediamine, reacting and curing to obtain composite hydrogel; and soaking the composite hydrogel in a glycerin / water mixed solution to obtain the composite hydrogel. When the composite hydrogel is used as a wound dressing, the composite hydrogel has the characteristics of good antibacterial activity, high sterilization efficiency, good anti-freezing and anti-drying performance and difficulty in generating drug resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation and application of a hydrogel, in particular to the preparation and application of a block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel. Background Art

[0002] Skin tissue is the first natural barrier of the human body facing the external environment. It plays a vital role in protecting important organs and regulating metabolism. It also plays the role of communicating between the human microenvironment and the external environment.

[0003] However, skin damage is often caused in daily life, accidents, diseases and trauma, which causes the skin to lose its basic protective mechanism and become vulnerable to invasion by pathogenic bacteria, leading to wound infection, inflammation, ulceration, etc., and even threatens the patient's life. Therefore, the wound healing process needs to be supplemented with antimicrobial agents to protect against bacterial invasion, such as antibiotics, metal ions, antimicrobial peptides or quaternary ammonium compounds. However, common antimicrobial agents have problems of toxicity, resistance and low selectivity, leading to the production of multi-drug resistant bacteria and causing secondary damage to the wound.

[0004] Hydrogels are widely used in the biomedical field as an emerging wound dressing. Among them, inherently antibacterial hydrogels, as new antibacterial materials, can not only effectively extend the antibacterial cycle, but also give them multiple functions such as anti-inflammatory, hemostasis, and promotion of cell growth, which can meet various needs of practical applications.

[0005] However, the antibacterial effect of this inherent antibacterial hydrogel that kills bacteria through active contact is limited, and there are requirements for the contact area and contact time. In addition, hydrogels are usually frozen under freezing conditions below 0°C, and lose water and harden under high temperature conditions above 50°C, making them unusable. Therefore, there are many obstacles in the actual application of current hydrogel dressings, which hinder the application of hydrogel dressings.

[0006] Based on this, it is necessary to study a new type of hydrogel wound dressing suitable for the treatment of infected skin wounds, and to effectively solve the problems of wound dressings' drug resistance and effectiveness in extreme environments, as well as the problem that the bactericidal effect of inherently antibacterial hydrogels is limited by contact conditions. This is of great significance to the development of the field of biomedical materials technology. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a preparation and application of a block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel. When used as a wound dressing, the composite hydrogel of the present invention has the characteristics of good antibacterial activity, high bactericidal efficiency, good antifreeze and anti-drying properties, and is not easy to produce drug resistance.

[0008] One of the technical solutions of the present invention:

[0009] Provided is a preparation method for a block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, comprising the following steps:

[0010] S1. Dissolve sodium alginate in water to prepare a solution with a concentration of 1-1.5wt%, then add NaIO4 solution, and react at room temperature in the dark for 3-5h to obtain an oxidized sodium alginate solution;

[0011] S2. Continue to add ethylene glycol to the oxidized sodium alginate solution of S1, terminate the reaction after 1.5-3 hours of reaction, and concentrate at 60-80°C, then dialyze and dry to obtain a white product, oxidized sodium alginate;

[0012] S3. acrylamide, 1-butyl-3-vinylimidazolium bromide, 3-acrylamide phenylboronic acid and quaternary ammonium salt chitosan are mixed and dissolved in water, and an initiator ammonium persulfate and a cross-linking agent N,N-methylenebisacrylamide are added in sequence, and stirred at room temperature for 1-2 hours; then the mixture is transferred to 55-65° C. and heated for 30-60 minutes; after the heating is completed, the mixture is transferred to room temperature for cooling to obtain a coolant;

[0013] S4. Dissolve the oxidized sodium alginate obtained in S2 in water, stir evenly, add to the coolant obtained in S3, continue stirring for 30-60 minutes, then add the polymerization accelerator N,N,N′,N′-tetramethylethylenediamine, stir evenly, pour into a mold, place at 70-80°C for cross-linking and curing, and obtain a composite hydrogel;

[0014] S5. The composite hydrogel prepared in S4 is soaked in a glycerol / water mixture for 20-24 hours, and then washed with water to remove excess surface substances to obtain a block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel.

[0015] Preferably, in the preparation of the aforementioned block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, in S1, the concentration of the NaIO4 solution is 70-90 mg / mL.

[0016] Preferably, in the preparation of the aforementioned block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, in S1 and S2, the volume ratio of the sodium alginate solution, the NaIO4 solution and the ethylene glycol is 8:1-1.2:0.03-0.04.

[0017] Preferably, in the preparation of the aforementioned block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, the dialysis time in S2 is 3 days, and the drying is freeze-drying.

[0018] Preferably, in the preparation of the aforementioned block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, the concentration in S2 is rotary evaporation concentration, the dialysis bag for dialysis has a Mw of 3500, and the water is changed four times a day during dialysis.

[0019] Preferably, in the preparation of the aforementioned block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, the mass ratio of acrylamide, 1-butyl-3-vinylimidazolium bromide, 3-acrylamidephenylboric acid and quaternary ammonium salt chitosan described in S3 is 1:0.6-1.0:0.05-0.15:0.05-0.08; the mass ratio of acrylamide, ammonium persulfate and N,N-methylenebisacrylamide is 125:1.8-2:0.8-1.

[0020] Preferably, in the preparation of the aforementioned block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, the mass ratio of oxidized sodium alginate to acrylamide added to the coolant in S4 is 20-30:100-300; the mass volume ratio of oxidized sodium alginate to N,N,N′,N′-tetramethylethylenediamine is 1 g:0.1-0.3 mL.

[0021] Preferably, in the preparation of the aforementioned block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, the volume ratio of the glycerol / water mixture in S5 is 4:1-3.

[0022] Preferably, in the preparation of the aforementioned block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, in S4, when the oxidized sodium alginate is dissolved in water, MXene or MXene-Ag-PDA is added, wherein the mass ratio of MXene or MXene-Ag-PDA, oxidized sodium alginate and acrylamide is 1:20-30:100-300.

[0023] The second technical solution of the present invention:

[0024] Provided is a use of the aforementioned block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel as a wound dressing.

[0025] Beneficial effects of the present invention:

[0026] 1. Compared with the prior art, the present invention uses block cationic polymer, oxidized sodium alginate and quaternary ammonium salt chitosan as hydrogel matrix materials, and introduces photothermal agent MXene-Ag-PDA to prepare composite hydrogel. The cationic groups contained in the hydrogel capture and kill bacteria through electrostatic action, and generate local heat to kill adsorbed and nearby residual bacteria under NIR irradiation, shortening the antibacterial cycle while improving the sterilization efficiency, solving the problem that the antibacterial activity of inherent antibacterial hydrogel is limited by contact area and contact time, and has the advantages of good antibacterial activity and high sterilization efficiency; at the same time, it promotes the wide application of hydrogel in the field of biomedical materials technology.

[0027] 2. Compared with the prior art, the composite hydrogel of the present invention kills bacteria synergistically through contact activity and photothermal action, does not kill bacteria by releasing antibacterial agents, and will not cause bacteria to develop drug resistance.

[0028] 3. Compared with the prior art, the present invention uses acrylamide, 1-butyl-3-vinylimidazolium bromide and 3-acrylamidephenylboronic acid to prepare a block cationic polymer, which not only gives the prepared hydrogel inherent antibacterial activity, but also gives it antifreeze and anti-drying properties; at the same time, the introduction of glycerol into the hydrogel by a simple immersion method further improves the antifreeze and anti-drying properties of the hydrogel, so that the hydrogel can function stably under extreme environments, solving the drug resistance of traditional wound dressings and their effectiveness under extreme environments.

[0029] 4. Compared with the prior art, the composite hydrogel of the present invention is a multi-network structure based on chemical cross-linking and dynamic cross-linking, which exhibits ideal mechanical strength in practical applications and is superior to most of the hydrogel dressings reported so far. Its self-healing ability can adapt to dynamic wounds.

[0030] In summary, the block cationic copolymer / quaternary ammonium salt chitosan composite hydrogel of the present invention, when used as a wound dressing, has high BSA adsorption capacity, antifreeze and anti-drying properties, free radical scavenging efficiency and antibacterial activity. When used in the treatment of infected wounds, it can control wound infection, reduce the production of pro-inflammatory factors, promote collagen deposition and neovascularization, and further promote wound healing. It is an ideal dressing for treating bacterial infected wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In the accompanying drawings, PNVAO represents that the amount of the photothermal agent incorporated in the composite hydrogel of the present invention is 0, PNVAO / M represents that the amount of the photothermal agent MXene incorporated is 5 mg, PNVAO / MA-P1 represents that the amount of the photothermal agent MXene-Ag-PDA incorporated is 5 mg, PNVAO / MA-P2 represents that the amount of the photothermal agent MXene-Ag-PDA incorporated is 10 mg, and HACC is quaternary ammonium salt chitosan;

[0032] Figure 1 Oxidized sodium alginate (OSA) 1 H NMR spectroscopy;

[0033] Figure 2 The hydrogel (AM-VBIMBr-AAPBA) prepared from acrylamide (AM), 1-butyl-3-vinylimidazolium bromide (VBIMBr) and 3-acrylamidephenylboronic acid (AAPBA) 13 C NMR spectroscopy;

[0034] Figure 3 FT-IR spectra of the composite hydrogel and its components of the present invention;

[0035] Figure 4 This is a photothermal photograph of the composite hydrogel of the present invention;

[0036] Figure 5 The antifreeze and anti-drying experimental photos of the PNVAO / MA-P1 composite hydrogel of the present invention;

[0037] Figure 6 is the adsorption amount of BSA by the composite hydrogel of the present invention;

[0038] Figure 7 is the DPPH free radical scavenging efficiency of the composite hydrogel of the present invention;

[0039] Figure 8 This is an antibacterial photo of the composite hydrogel treated for 30 minutes and irradiated with NIR for 10 minutes;

[0040] Fig. 9 It is the bacterial survival rate after 30min treatment with the composite hydrogel of the present invention and 10min NIR irradiation;

[0041] Fig.10 The contact antibacterial activity of the composite hydrogel of the present invention before and after NIR light irradiation;

[0042] Fig.11 The in vitro cell compatibility of the composite hydrogel of the present invention;

[0043] Fig.12 Photos of wound healing and wound healing area of ​​mice infected with the virus;

[0044] Fig.13 Histological analysis images of composite hydrogels: H&E (a), Masson (b), TNF-α and IL-1β (c), CD31 and α-SMA (d) (blue arrows indicate neutrophils, red arrows indicate hair follicles, and yellow arrows indicate positive expression).

[0045] By attaching Figure 1-13It is known that the present invention obtains a block cationic polymer ( Figure 2 ), oxidized sodium alginate ( Figure 1 ) and quaternary ammonium salt chitosan as the matrix materials of the antibacterial hydrogel, and introduced modified MXene (MXene-Ag-PDA) into the hydrogel as a photothermal agent to obtain a multifunctional composite hydrogel (PNVAO / MAP) with photothermal effect and inherent antibacterial activity ( Figure 3 and Figure 4 The hydrogel has a multi-crosslinked structure. The amino groups contained in the cationic polymer and HACC form dynamic imine bonds with the aldehyde groups contained in OSA. The boric acid groups contained in AAPBA can form dynamic crosslinking bonds. The infrared spectra of PNVAO / M and PNVAO / MAP composite hydrogels show that the peak of the IR spectrum is 1315 cm -1 The COC absorption peak appears, and the peak intensity increases with the modification of the photothermal agent, indicating that there is a covalent interaction between the hydrogel matrix and the photothermal agent ( Figure 3 The hydrogel dressing exhibits excellent antifreeze and anti-desiccation properties ( Figure 5 )、High BSA adsorption capacity ( Figure 6 ), antioxidant properties ( Figure 7 ), excellent antibacterial activity ( Figure 8 and Fig. 9 ) and biocompatibility ( Fig.11 The cationic groups contained in the composite hydrogel of the present invention capture and kill bacteria through electrostatic action, and generate local heat to kill adsorbed and nearby residual bacteria under NIR irradiation, so that the sterilization rate of MDR E.coli and MRSA is as high as 100%, shortening the antibacterial cycle while improving the sterilization efficiency ( Fig. 9 At the same time, the hydrogel does not release antibacterial agents to prevent bacteria from developing drug resistance ( Fig.10 ). In addition, the application of composite hydrogel dressings in the treatment of infected wounds can control wound infection, reduce the production of pro-inflammatory factors, promote collagen deposition and neovascularization, and thus promote wound healing ( Fig.12 and Fig.13 ), is an ideal dressing for treating bacterially infected wounds. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.

[0047] Embodiments of the present invention

[0048] Example 1

[0049] A block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel is prepared by the following steps:

[0050] S1. 1.5 g of sodium alginate (SA) was dissolved in 150 mL of deionized water to prepare a 1 wt% solution, and then 20 mL of NaIO4 solution (prepared by dissolving 1.6 g of NaIO4 in 20 mL of deionized water) was added dropwise, and the reaction was carried out at room temperature in the dark for 4 h to complete the oxidation of SA;

[0051] S2. Then, 0.6 mL of ethylene glycol was added to continue the reaction for 1.5 h to terminate the reaction, and the solution was concentrated to 50 mL by rotary evaporation at 60 ° C. The solution was placed in a dialysis bag (Mw = 3500) and dialyzed for 3 days. The water was changed 4 times a day. After the dialysis, the white product of oxidized sodium alginate (OSA) was obtained by freeze drying;

[0052] S3. Dissolve 1 g of acrylamide (AM), 0.8 g of 1-butyl-3-vinylimidazolium bromide (VBIMBr), 0.1 g of 3-acrylamide phenylboronic acid (AAPBA) and 0.05 g of quaternary ammonium salt chitosan (HACC) in 1 mL of deionized water, add 0.016 g of initiator ammonium persulfate (APS) and 0.008 g of cross-linking agent N,N-methylenebisacrylamide (MBA) in turn, stir at room temperature for 1 h; then transfer to a 60 °C water bath and heat Heat for 30 minutes, and keep magnetic stirring during the whole process; after heating, transfer the above mixture to room temperature for cooling; weigh 0.15g OSA and dissolve it in 1mL deionized water, then add the OSA solution dropwise into the above mixture and stir for 30 minutes, and add 30μL polymerization promoter N,N,N′,N′-tetramethylethylenediamine (TEMED), stir evenly, pour into a mold, place at 75℃ for cross-linking and curing into gel, and wash the prepared composite hydrogel with a large amount of deionized water to remove unreacted substances;

[0053] S4. The composite hydrogel was placed in a glycerol / water (glycerol: water = 4:1) mixed solution and soaked for 24 hours. After that, it was washed with deionized water to remove excess substances on the surface to obtain a composite hydrogel PNVAO.

[0054] Example 2

[0055] The method of this embodiment is similar to that of the embodiment, with the only difference being that when OSA is dissolved in water in S3, 5 mg MXene is also added, and the resulting composite hydrogel is PNVAO / M.

[0056] Example 3

[0057] The method of this embodiment is similar to that of the embodiment, with the only difference being that when OSA is dissolved in water in S3, 5 mg MXene-Ag-PDA is also added, and the resulting composite hydrogel is PNVAO / MA-P1.

[0058] Example 4

[0059] The method of this embodiment is similar to that of the embodiment, except that: when OSA is dissolved in water in S3, 10 mg MXene-Ag-PDA is also added, and the resulting composite hydrogel is PNVAO / MA-P2.

[0060] The MXene and MXene-Ag-PDA used in the above Examples 2-4 are both existing photothermal agents, which can be prepared by existing methods or purchased as commercial products.

[0061] Example 5

[0062] The composite hydrogel prepared in Examples 1-4 is used as a wound dressing, and its application method is consistent with the application method of existing wound hydrogel dressings.

[0063] Example 6

[0064] A block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel is prepared by the following steps:

[0065] S1. 1.2 g of sodium alginate (SA) was dissolved in 100 mL of deionized water to prepare a 1.2 wt% solution, and then 12.5 mL of NaIO4 solution (prepared by dissolving 1.4 g of NaIO4 in 20 mL of deionized water) was added dropwise, and the reaction was carried out at room temperature in the dark for 3 h to complete the oxidation of SA;

[0066] S2. Then, 0.375 mL of ethylene glycol was added to continue the reaction for 2 h to terminate the reaction, and the solution was concentrated to 50 mL by rotary evaporation at 70 ° C. The solution was placed in a dialysis bag (Mw = 3500) and dialyzed for 3 days. The water was changed 4 times a day. After the dialysis, the white product of oxidized sodium alginate (OSA) was obtained by freeze drying;

[0067] S3. Dissolve 1 g of acrylamide (AM), 0.6 g of 1-butyl-3-vinylimidazolium bromide (VBIMBr), 0.05 g of 3-acrylamide phenylboronic acid (AAPBA) and 0.06 g of quaternary ammonium salt chitosan (HACC) in 1 mL of deionized water, add 0.014 g of initiator ammonium persulfate (APS) and 0.006 g of cross-linking agent N,N-methylenebisacrylamide (MBA) in turn, stir at room temperature for 2 h; then transfer to a 55 °C water bath. Heating for 60 minutes, maintaining magnetic stirring throughout the process; after heating, transferring the above mixture to room temperature for cooling; weighing 0.07g OSA and dissolving it in 1mL deionized water, then adding the OSA solution dropwise into the above mixture and stirring for 50 minutes, and adding 7μL polymerization promoter N,N,N′,N′-tetramethylethylenediamine (TEMED), stirring evenly, pouring into a mold and placing it at 70°C for cross-linking and curing into a gel, and the prepared composite hydrogel was washed with a large amount of deionized water to remove unreacted substances;

[0068] S4. The composite hydrogel was placed in a glycerol / water (glycerol: water = 4:2) mixture and soaked for 20 hours. After that, it was washed with deionized water to remove excess substances on the surface to obtain a composite hydrogel PNVAO.

[0069] Example 7

[0070] A block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel is prepared by the following steps:

[0071] S1. 1.5 g of sodium alginate (SA) was dissolved in 100 mL of deionized water to prepare a 1.5 wt% solution, and then 15 mL of NaIO4 solution (prepared by dissolving 1.8 g of NaIO4 in 20 mL of deionized water) was added dropwise, and the reaction was carried out at room temperature in the dark for 5 h to complete the oxidation of SA;

[0072] S2. Then, 0.5 mL of ethylene glycol was added to continue the reaction for 3 h to terminate the reaction, and the solution was concentrated to 50 mL by rotary evaporation at 80 ° C. The solution was placed in a dialysis bag (Mw = 3500) and dialyzed for 3 days. The water was changed 4 times a day. After the dialysis, the white product of oxidized sodium alginate (OSA) was obtained by freeze drying;

[0073] S3. Dissolve 1 g of acrylamide (AM), 1 g of 1-butyl-3-vinylimidazolium bromide (VBIMBr), 0.15 g of 3-acrylamidephenylboronic acid (AAPBA) and 0.08 g of quaternary ammonium salt chitosan (HACC) in 1 mL of deionized water, add 0.015 g of initiator ammonium persulfate (APS) and 0.007 g of cross-linking agent N,N-methylenebisacrylamide (MBA) in turn, stir at room temperature for 1.5 h; then transfer to a water bath at 65 °C. Heating for 40 minutes, maintaining magnetic stirring throughout the process; after heating, transferring the above mixture to room temperature for cooling; weighing 0.3g OSA and dissolving it in 1mL deionized water, then adding the OSA solution dropwise into the above mixture and stirring for 60 minutes, and adding 90μL polymerization promoter N,N,N′,N′-tetramethylethylenediamine (TEMED), stirring evenly, pouring into a mold and placing it at 80°C for cross-linking and curing into a gel, and the prepared composite hydrogel was washed with a large amount of deionized water to remove unreacted substances;

[0074] S4. The composite hydrogel was placed in a glycerol / water (glycerol: water = 4:3) mixture and soaked for 22 hours. After that, it was washed with deionized water to remove excess substances on the surface to obtain a composite hydrogel PNVAO.

[0075] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Preparation of a block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel, characterized in that: The steps include: S1. Dissolve sodium alginate in water to prepare a solution with a concentration of 1-1.5wt%, then add NaIO4 solution, and react at room temperature in the dark for 3-5h to obtain an oxidized sodium alginate solution; S2. Continue to add ethylene glycol to the oxidized sodium alginate solution of S1, terminate the reaction after 1.5-3 hours of reaction, and concentrate at 60-80°C, then dialyze and dry to obtain a white product, oxidized sodium alginate; S3. acrylamide, 1-butyl-3-vinylimidazolium bromide, 3-acrylamide phenylboronic acid and quaternary ammonium salt chitosan are mixed and dissolved in water, and an initiator ammonium persulfate and a cross-linking agent N,N-methylenebisacrylamide are added in sequence, and stirred at room temperature for 1-2 hours; then the mixture is transferred to 55-65° C. and heated for 30-60 minutes; after the heating is completed, the mixture is transferred to room temperature for cooling to obtain a coolant; S4. Dissolve the oxidized sodium alginate obtained in S2 in water, stir evenly, add to the coolant obtained in S3, continue stirring for 30-60 minutes, then add the polymerization accelerator N,N,N′,N′-tetramethylethylenediamine, stir evenly, pour into a mold, place at 70-80°C for cross-linking and curing, and obtain a composite hydrogel; S5. The composite hydrogel prepared in S4 is soaked in a glycerol / water mixture for 20-24 hours, and then washed with water to remove excess surface substances to obtain a block cationic copolymer quaternary ammonium salt chitosan composite hydrogel.

2. The preparation of the block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel according to claim 1, characterized in that: In the S1, the concentration of the NaIO4 solution is 70-90 mg / mL.

3. The preparation of the block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel according to claim 1, characterized in that: In S1 and S2, the volume ratio of the sodium alginate solution, the NaIO4 solution and the ethylene glycol is 8:1-1.2:0.03-0.

04.

4. The preparation of the block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel according to claim 1, characterized in that: The dialysis time in S2 is 3 days, and the drying is freeze-drying.

5. The preparation of the block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel according to claim 1, characterized in that: The concentration in S2 is rotary evaporation concentration, the dialysis bag for dialysis has Mw=3500, and the water is changed 4 times a day during dialysis.

6. The preparation of the block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel according to claim 1, characterized in that: The mass ratio of acrylamide, 1-butyl-3-vinylimidazolium bromide, 3-acrylamidephenylboric acid and quaternary ammonium salt chitosan described in S3 is 1:0.6-1.0:0.05-0.15:0.05-0.08; the mass ratio of acrylamide, ammonium persulfate and N,N-methylenebisacrylamide is 125:1.8-2:0.8-1.

7. The preparation of the block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel according to claim 1, characterized in that: The mass ratio of oxidized sodium alginate to acrylamide added to the coolant in S4 is 20-30:100-300; the mass volume ratio of oxidized sodium alginate to N,N,N′,N′-tetramethylethylenediamine is 1 g:0.1-0.3 mL.

8. The preparation of the block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel according to claim 1, characterized in that: The volume ratio of the glycerol / water mixture in S5 is 4:1-3.

9. The preparation of the block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel according to claim 1, characterized in that: In S4, when oxidized sodium alginate is dissolved in water, MXene or MXene-Ag-PDA is added, wherein the mass ratio of MXene or MXene-Ag-PDA, oxidized sodium alginate and acrylamide is 1:20-30:100-300.

10. Use of the block cationic copolymer / quaternary ammonium salt chitosan-based composite hydrogel according to any one of claims 1 to 9 as a wound dressing.

Citation Information

Cited By

  • Preparation method of sodium alginate-based gradient hydrogel sensor

    CN119431693A

  • Quaternary ammonium salt modified chitosan-based composite hydrogel and preparation method thereof

    CN119775641A

  • Hemostatic dressing for easing pain and diminishing inflammation as well as preparation method and application thereof

    CN121243442A

  • Hydrogel wound dressing capable of rapidly stopping bleeding and preparation method thereof

    CN121313934A